Incidental findings during lung cancer screening by low-dose computed tomography - Aleksandr E. Nikolaev; Viktor A. Gombolevskiy; Anna P. Gonchar; Arsen N. Shapiev; Albina Sh. Laypan; Sergey P. Morozov (Туберкулез и болезни лёгких)
In Moscow in 2017, the project named Moscow Screening for Lung Cancer was started using low-dose computed tomography (LDCT) for selective screening for lung malignant tumors in the out-patient facilities and polyclinics.The main goal of the project: to improve early detection of lung cancer and reduce mortality caused by this disease in the long term.The objective of the study: to assess the importance of incidental findings during selective screening for lung cancer by LDCT in Moscow.Subjects and Methods. The retrospective study included 254 randomly selected LDCT, which were performed as a part of the screening program. During the repeated examination of images and protocols, all abnormalities were taken into account (but for foci in the lungs evaluated as per LungRADS-2014).Results. When analyzing the dissemination and character of incidental findings, detected by LDCT screening, it was found out that such findings had high clinical and/or predictive value in the majority of cases. The following disorders were detected the most often (% of those with incidental finding): coronary artery calcium - 49.3%; thickening of bronchial walls - 34.9%; bronchiectasis - 34.9%; emphysema - 21.6%.During primary interpretation of LDCT results, less attention was paid to description of abnormalities but for foci evaluated as per Lung RADS-2014. Further research and organization are needed to provide detection and reasonable routing for those with incidental findings.Conclusions. Incidental findings occur in 87.1% of cases during selective screening for lung cancer by LDCT. The majority of incidental findings are located in the cardio-vascular (75.4%) and respiratory (68.3%) systems, and they possess clinical and predictive value.